A computational simulation of heat transfer to separation air flow in a concentric pipe - C. S., Oon; Hussein, Togun; Kazi, Md. Salim Newaz, Dr.; Ahmad Badarudin, Mohamad Badry, Dr.; Mohd Nashrul, Mohd Zubir (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.